Biological age is better than chronological as predictor of 3-month outcome in ischemic stroke. (22nd August 2017) - Soriano-Tárraga, Carolina; Mola-Caminal, Marina; Giralt-Steinhauer, Eva; Ois, Angel; Rodríguez-Campello, Ana; Cuadrado-Godia, Elisa; Gómez-González, Alejandra; Vivanco-Hidalgo, Rosa M.; Fernández-Cadenas, Israel; Cullell, Natalia; Roquer, Jaume; Jiménez-Conde, Jordi
Abstract : Objective: To analyze the effect of age-related DNA methylation changes in multiple cytosine-phosphate-guanine (CpG) sites (biological age [b-age]) on patient outcomes at 3 months after an ischemic stroke. Methods: We included 511 patients with first-ever acute ischemic stroke assessed at Hospital del Mar (Barcelona, Spain) as the discovery cohort. Demographic and clinical data, including chronological age (c-age), vascular risk factors, initial stroke severity, recanalization treatment, and previous and 3-month modified Rankin Scale (p-mRS and 3-mRS, respectively) were registered. B-age was estimated with an algorithm, based on DNA methylation in 71 CpGs. Bivariate analysis determined variables associated with 3-mRS for inclusion in ordinal multivariate analysis. Results: After ordinal regressions for 3-month ischemic stroke outcome (3-mRS), b-age was associated with outcome (odds ratio 1.04 [95% confidence interval 1.01–1.07]), nullifying c-age. Stepwise regression kept b-age, basal NIH Stroke Scale, sex, p-mRS, and recanalization treatment as better explanatory variables, instead of c-age. These results were successfully replicated in an independent cohort. Conclusions: B-age, estimated by DNA methylation, is an independent predictor of ischemic stroke outcome regardless of chronological years.